Improving Fertiliser Use Efficiency In Sesamum In Onattukara Tract - Regy VJ (Department of Agronomy, College of Agriculture, 1996)
An experiment was conducted in the summer rice fallows of the Rice Research station, Kayamkulam during 1995 to study the effect of two levels of nitrogen (22.5, and 30 kg N ha-1) three levels of potassium (0, 22.5 and 30 Kg K2O ha-1) and two methods of application (75 per cent) each of nitrogen and potassium as basal and 25 per cent each of nitrogen and potassium as foliar spray at branching (m1), 50 per cent each of nitrogen and potassium as basal and 50 per cent each of nitrogen and potassium as foliar spray as to equal splits at branching and just before flowering (m2) on the growth, yield, oil and protein content, chemical composition of oil cake, nutrient status of soil after the experiment and economics. The study revealed that nitrogen affected LAI, LAD and NAR, but failed to have any influence on height of the plants, number of branches plant-1, height at which first bearing node formed, RGR, CGR, yield attributing characters, yield and oil content. Test weight, net return, benefit cost ratio, protein content, uptake of nitrogen, phosphorus and